Differentiation of smooth muscle cells from mesenchymal stem cells - Aungkura Jerareungrattana (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Blood vessel tissue engineering has arisen to serve the problem of vascular diseases. The blood vessel tissue engineering process requires stem cell technology for autologous transplantation. There are many sources of stem cells in adult humans but the most popular are bone marrow stem cells (BMSCs) or mesenchymal stem cells. In this study, for further tissue engineering application, the BMSCs have been induced by TGF-β and/or retinoic acid (RA) for differentiation into smooth muscle cells. The smooth muscle alpha actin (SM α-actin), the earliest smooth muscle cell marker, was observed in induced BMSC in all treatments. The TGF-β1 treatment showed morphological change appearing as a ribbon shape with intracellular stress fiber. The RA treatment showed spindle shaped cells with a tendency to cluster which is similar to the combination and serial addition of TGF-β1 and RA. The expression of SM α- actin was demonstrated using immunofluorescent technique and Western blot analysis. Using TGF-β1 and 0.01μM RA a highly positive reaction for SM α-actin was shown in immunofluorescent analysis. The expression level of SM α-actin was evaluated by Western blot and densitometric analysis. It was shown that TGF-β1 can promote a high expression of SM α-actin. The RA showed good enhanced protein expression at 0.01 μM dose. The BMSCs treated with TGF-β1 for 24hrs and then followed by RA treatment on day 3 promoted expression of SM α-actin at higher degrees than other treatments but on day 5 this protein became lower. The combination at TGF-β1 and RA showed the lowest expression of SM α-actin. This data shows that both TGF-β1 and 0.01μM RA can promote SMC characteristics from BMSC. The study shows that TGF-β1 and RA may regulate SM α-actin expression differently. The BMSCs have shown to be a good source for SMC differentiation. The retinoic acid is another factor which can promote this step.